Regrowth of caatinga vegetation after slashing and burning, at Serra Talhada, PE, Brazil - Valadares de Sá Barretto Sampaio, Everardo; de Lima Araújo, Elcida; Hernán Salcedo, Ignácio; Tiessen, Holm (Pesquisa Agropecuaria Brasileira, 1998)
Regeneration of the native vegetation after slashing and burning is important in the establishment of an adequate management system in fire wood producing and shifting agriculture areas. To monitor this regeneration, measurements of aboveground biomass and plant density were made, for every species, in Serra Talhada, PE, 2 months, 2 years and 6 years after slashing without burning (SQ) and burning with increasing fire intensities (Q1, Q2 and Q3). Plants coppiced more in SQ (94% of the initial 5810 plants ha-1) than with burning (43, 21 and 10%). Density decreased at 2 years and increased again at 6 years and was highest in SQ and lowest in Q3. Biomasses increased with time and were lowest with burning (6 years, SQ = 29.7 and Q3 = 16.8 Mg ha-1). There was 2 Mg of biomass per m2 of basal area. The number of species (initial 15) decreased after 2 months (SQ = 12 and Q3 = 8), peaked at 2 years (Q3 = 15, some pioneers) and decreased again at 6 years (Q3 = 12). Among the species with highest initial densities, C. sonderianus and Mimosa sp. were favored in the competition after slashing and burning while C. leucocephala was disfavored.